Withering tights - Rennison, Louise (HarperTeen, 2011)
Self-conscious about her knobby knees but confident in her acting ability, fourteen-year-old Tallulah spends the summer at a Yorkshire performing arts camp that, she is surprised to learn, is for girls only.